The right of conversion and its effect in relation to human rights: a case study of Malaysia and Indonesia - Mohd Zin, Najibah (s.n, 2012)
This project discusses one aspect of religious freedom that is to answer the controversial legal argument of whether there is such right to convert to other faith in Islam from human rights perspectives and the Islamic human rights.